2011
DOI: 10.1038/jhh.2011.42
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and psychosocial correlates of nondipping blood pressure pattern among middle-aged men and women at work

Abstract: The underlying pathogenetic mechanisms of nondipping blood pressure (BP) pattern are not completely understood. Especially the role of psychosocial correlates remains unclear. The aim was to assess the association between nondipping BP pattern, behavioural and psychosocial factors in a sample of working men and women. The study sample included 167 working men and women aged 40-64 years from the BELSTRESS cohort. Sociodemographic, behavioural and psychosocial factors were assessed by self-administered questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Several studies (12, 13, 26, 27) have shown that blunted nighttime BP dipping, or non-dipping, is associated with end-organ damage, increased risk of future cardiovascular events and higher cardiovascular morbidity and mortality. One recent Belgian study suggests that job strain is an independent risk factor for non-dipping (14). Our study supports this possibility by demonstrating that men with high job strain had significantly blunted SBP and PP dipping compared to men with low job strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (12, 13, 26, 27) have shown that blunted nighttime BP dipping, or non-dipping, is associated with end-organ damage, increased risk of future cardiovascular events and higher cardiovascular morbidity and mortality. One recent Belgian study suggests that job strain is an independent risk factor for non-dipping (14). Our study supports this possibility by demonstrating that men with high job strain had significantly blunted SBP and PP dipping compared to men with low job strain.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported that hypertensive patients with a non-dipping BP pattern (<10% nighttime BP fall) show more end-organ damage and higher cardiovascular morbidity and mortality than those who show normal BP dipping (≄10% nighttime BP fall)(12, 13). However, there are few studies that have explored the relationship between job strain and blunted nighttime BP dipping (14, 15). The present study was designed to evaluate the impact of job strain on nighttime BP dipping in a study sample of untreated men and women with high normal or mildly elevated BP.…”
Section: Introductionmentioning
confidence: 99%
“…Confounding might also be present in other studies due to a lack of control for cardiovascular risk factors. For example, some studies did not control for age (125,132,144,146,174) or family history of CVD (61 studies) (23, 44, 124-129, 131-141, 153, 155-159, 161-168, 171, 174, 178, 180, 181, 183, 185-189, 192-194, 214, 223, 224) (tables A-C), which constitute major risk factors for high BP. Residual confounding might also have resulted from the fact that none of the studies on job strain controlled for ERI or vice-versa.…”
Section: (Tables A-c)mentioning
confidence: 99%
“…Furthermore, it has been suggested that non-dipping is also associated with other non-cardiovascular symptoms such as psychosocial factors. [11] Non-dipping is common in PD, and ranges in prevalence from 40% [12] to 92% [13]. The reasons for a blunted/reversed circadian blood pressure rhythm in PD can include several factors, including pathological entities, such as disorders of nocturnal movement, obstructive sleep apnea (OSAS), supine hypertension and reduced quality of sleep.…”
Section: Introductionmentioning
confidence: 99%